Spectacles against the Swastika: Informal Education through Meyer Weisgal's 1930s Theatrical Productions. Issue 1 (2nd January 2020) - Samson, Maxim G. M.
Abstract : Despite increased attention among geographers to the diversity of spaces that can constitute informal sites of education, theater in general and spectacles more specifically have garnered relatively little geographical interest. In response, this paper draws upon Paulo Freire's philosophy to examine how the two major productions of the Zionist activist Meyer Weisgal— The Romance of a People and The Eternal Road —aimed to challenge historic representations of Jews by more powerful groups while raising funds and support for the Zionist cause. Although the shows were unable to hinder the Nazi threat, Freire's pedagogy demonstrates their power in enabling those subjected to prejudice to develop a voice, raise awareness of social and political concerns, and attract wider support. Consequently, spectacles' educational potential in disseminating ideologies and facilitating learning and empathetic relations within and between groups must be acknowledged.